2019
DOI: 10.1186/s12933-019-0935-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and diagnostic biomarkers for gestational diabetes and its associated metabolic and cardiovascular diseases

Abstract: Gestational diabetes mellitus (GDM) is defined as the presence of high blood glucose levels with the onset, or detected for the first time during pregnancy, as a result of increased insulin resistance. GDM may be induced by dysregulation of pancreatic β-cell function and/or by alteration of secreted gestational hormones and peptides related with glucose homeostasis. It may affect one out of five pregnancies, leading to perinatal morbidity and adverse neonatal outcomes, and high risk of chronic metabolic and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 169 publications
3
90
0
Order By: Relevance
“…The change in methylation patterns affects glucose concentration by altering peripheral insulin sensitivity during pregnancy [44,45]. Finally, changes in glucose homeostasis in healthy pregnant women might be due to the metabolic induction change in the hypothalamus [46,47]. Our results of the associations between tra c indicators as well as PMs exposures and glucose intolerance could be explained by one or all of the above mechanisms.…”
Section: Biological Plausibilitymentioning
confidence: 66%
“…The change in methylation patterns affects glucose concentration by altering peripheral insulin sensitivity during pregnancy [44,45]. Finally, changes in glucose homeostasis in healthy pregnant women might be due to the metabolic induction change in the hypothalamus [46,47]. Our results of the associations between tra c indicators as well as PMs exposures and glucose intolerance could be explained by one or all of the above mechanisms.…”
Section: Biological Plausibilitymentioning
confidence: 66%
“…Several studies have provided the evidence of myocardial damage in the early asymptomatic period among patients with IGM [12][13][14]. Additionally, some reports also indicated that diabetic patients could have heart damage in results of its complications like diabetic cardiomyopathy [15, 16]. Therefore, a further understanding of the cardiovascular risk associated with IGM will help to risk stratification and preventive strategies in pre-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, diabetic patients could have structural and/or functional modifications in the myocardial tissue such as lacking of insulin sensitivity and glucose assimilation. As a compensatory mechanism, H-FABP may increase when fatty acid uptake increases in heart to supply more adenosine triphosphate (ATP) [15,16]. On the other hand, there is evidence that abnormal of cardiac microvascular circulation caused by metabolic disorders might induce cardiomyocyte injury and impair cardiac function [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that there are two mechanisms that might be responsible for the increased EAT thickness in GDM patients. Firstly, the higher levels of retinol-binding protein 4 and lower levels of adiponectin secreted by adipose tissue, including EAT, prior to 16 GW [25,26], could cause insulin resistance (IR), the main mechanisms underlying GDM [27]. Secondly, during the first-second trimester, EAT releases higher levels of pro-inflammatory adipokines (RBP4, hs-CRP, fatty acid-binding protein-4, leptin, and visfatin), and lower levels of anti-inflammatory adipokines (omentin-1 and adiponectin); these may participate in the chronic low-grade state of inflammation that has previously been confirmed to be associated with GDM [26,28].…”
Section: Discussionmentioning
confidence: 99%